Post-fire behaviour and resistances of S690 high strength steel welded I-section stub columns - Su, Andi (2022)
The cross-sectional behaviour and residual compression resistances of S690 high strength steel welded I-section stub columns after exposure to elevated temperatures up to 950 °C have been investigated, underpinned by testing and numerical modelling, and fully presented in this paper. The testing programme used three S690 high strength steel welded I-sections — I-80×60×5, I-100×100×5 and I-140×70×5, and for each aforementioned I-section, seven geometrically identical stub column specimens were prepared and tested after exposure to different levels of elevated temperature (including 30 °C, 300 °C, 600 °C, 700 °C, 800 °C, 900 °C and 950 °C). This was followed by a numerical modelling programme, where finite element models were developed and validated against the post-fire stub column test results and then adopted to conduct parametric studies to generate further numerical data over a wide range of cross-section dimensions. Given that there are currently no available design standards for high strength steel structures after exposure to elevated temperatures, the relevant ambient temperature design rules, as set out in the European code, American specification and Australian standard, were assessed, using post-fire material properties, for their applicability to S690 high strength steel welded I-section stub columns after exposure to elevated temperatures up to 950 °C. The results of the assessments revealed that (i) all three sets of codified ambient temperature slenderness limits for internal and outstand plate elements in compression are generally accurate when used for cross-section classification of S690 high strength steel welded I-section stub columns after exposure to elevated temperatures and (ii) the ambient temperature local buckling design rules (i.e. slenderness limits in combination with effective width methods), as set out in the three considered design standards, are capable of providing accurate and consistent post-fire compression resistance predictions for S690 high strength steel welded I-section stub columns.